(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To survey the current status of antibiotic use and the level of knowledge regarding antibiotic use of residents in Da Nang City and detemine the related factors. Research Subjects and Methods: A cross-sectional description was conducted among 845 household representatives in Da Nang City. Results: The results showed that most of the participants (55.6%) reported they took antibiotics within the past year. Among those who used antibiotics, 43.5% claimed that their usage was following a physician’s prescription, and only 384 people (48.4%) received instructions on how to use antibiotics. The average score of antibiotic knowledge of people in Da Nang City is 8.87 ± 3.15 with 62.6% of residents showing good knowledge about antibiotic use. The findings also showed that age and marital status are significantly related to the level of knowledge about antibiotic use. Individuals who follow a physician’s prescription and receive instructions on antibiotic use are related to better knowledge about antibiotic use. Conclusion and recommendations: The results show that the proportion of people using antibiotics appropriately remained low, despite the majority of people having good knowledge about antibiotic use. Therefore, it is necessary to strengthen health education through programs to improve knowledge about the proper use of antibiotics for the public.